La Universidad y su crítica. Movimiento estudiantil, reforma universitaria y mercado de trabajo (1975-2003) - Rodríguez López, Emmanuel (Logos. Anales del Seminario de Metafísica, 2003)
The University has been one of the historicals objects of social critique. The pourpuse of this article is to offer a historical brief of critical rethoriques of the universitary institution relay on its social functions and his hability to promote student movement.
Keywords: University; Labour market; Student movement; Basic income; Selfeducation